Studies for a place: The House of Leda (two-channel video, installation) - Pericleous, Vicky (My University, 2024)
COOKIES explores the concepts of consent, acceptance, care and surveillance as they are shaped in the ever-changing digital environment. The invited artists present different stories about the Internet, which is approached as both an experience and a medium while exploring the nature and use of the information we create within it. ​The exhibition focuses on the data we produce at any given moment through paintings, video projections, films, and installations. It explores how digital technology reshapes our understanding of the world and raises questions about the power dynamics between people and technology.
Cookies
Keywords: Arts; Exhibitions; Digital Environments; Digital technologies & Power Structures; Narrative and Histories in Digital Experiences